A Comparison of Impacts of Climate Change on Urban Poverty and Rural Poverty in the North-West China - Zhou, Xiaoxue; Chen, Jiancheng (International Journal of Management and Sustainability, 2019)
This paper explores the contrast between urban poverty and rural poverty under climate change in north-west China based on association theory. In order to effectively evaluate the different impacts of climate change on rural and urban poverty, this paper establishes a dynamic GMM regression model of climate change, uses the north-west region panel data to clarify the relationship of ecological environment, carbon emissions and poverty alleviation in north-west China. The empirical test results show there exists an inverted U-shaped curve relationship between carbon emissions and the rural poor income, but there is no significant correlation between carbon emissions and that of the urban poor. There is an obvious intertemporal transmission of poverty, and that of rural poverty is more obvious than urban poverty. Economic growth is still the most important power source of poverty reduction in urban and rural areas in north-west China, however, the number of years of education had no obvious influences on the income of urban and rural poor population.